INTELKAM UNIT ROLE IN COMBATING NARCOTICS ABUSE IN BOGOR BY DECREE NO NATIONAL POLICE SKEP / 37 / I / 2005 (Studies In Bogor City Police) - Endeh Suhartini1; Ade Rahmat; Ani Yumarni (JURNAL HUKUM DE'RECHTSSTAAT, 2015)
ABSTRACT In the Decree of the Chief of Police No. Pol Skep / 37 / I / 2005 dated January 31, 2005 on Guidelines for Environmental Security Intelligence at the Indonesian Police, stated that security intelligence is intelligence that is implemented in carrying out the principal task of the police to bring internal security. Implementation of the activities and operations of security intelligence is to early prevention, early detection and implementation of early warning in accordance with the vision and mission of the security intelligence. Throughout 2014 the number of drug cases occurring among drug cases increased from 108 cases to 168 cases or by 55.6 percent.The objectives to be achieved in this thesis are: 1) To determine and analyze the role of Unit Intelkam in combating drug abuse in the city of Bogor by the Decree of the Chief of Police No. Skep / 37 / I / 2005. 2) To know and analyze the obstacles encountered Intelkam Force in combating drug abuse in the city of Bogor, and 3) To know and analyze the efforts made Intelkam Unit in overcoming obstacles to overcome combating abuse of narcotics in the city of Bogor. The method used normative juridical research method that is conceived as the norm of law, rules, principles or dogmas.The study concluded that the role of Bogor City Police Intelkam has shown good performance in dealing with drug abuse in the region combating the city of Bogor this is done in order to get results and optimum efficiency in the process of investigating criminal cases by way of supervision open or closed in preventing abuse of the use of narcotics.